Consumers' perceptions and preferences for sustainably-produced fruits and vegetables: the case of organic, local, and small farm - Whorton, Carly (Kansas State University, 2011)
This study focuses on determining what key differences predispose a consumer to regularly purchase and be willing to pay a premium for sustainably-produced fruits and vegetables. Organic, local, and small farm are the three cases used in the study. The research used a structured questionnaire to conduct an online survey of U.S. internet users with email addresses in the spring of 2011 with logit and ordered logit regression used as the analytical tools. Cost was the most important factor for consumers who did not purchase organic and local products more frequently while unavailability was the principal reason for not consuming produces from small farms. The study showed consumers of small farm products often (98.5 percent of the time) consume local fruits and vegetables also but not the other way around. The relevant socio-economic factors for determining organic purchasing frequency were gender, household size, and education. For small farm they were the ability to influence local change and the respondents’ frequency of purchase of local products. Socio-economic characteristics did not prove to be a factor in local purchasing decisions. Regular purchasers of organic fruits and vegetables provided a consistent perception of organic products with the USDA certified organic definition. Local consumers reported that taste and freshness are the most defining characteristics of local products while small farm consumers could not provide a clear picture of the definitional statements defining fruits and vegetables produced by a small farm. This implied that there is need for more work by small farm producers to differentiate themselves in the market. On the contrary, both local and organic producers have a clear point of differentiation to reach their customers. Industry marketing efforts can be greatly improved by focusing on the characteristics of the consumers they are trying to reach. Our results can be further investigated by completing the following recommendations. First, to conduct more targeted studies such as interviews or focus groups, second, to gain a deeper understanding of how consumers perceive these attributes and third to conduct a comprehensive study on the similarities and differences between small farm and local consumers.
Keywords: Consumer Perception; Consumer Preferences; Organic; Local; Small Farm; Survey; Agriculture, General (0473); Economics, Agricultural (0503); Sustainability (0640)